EARLY OUTCOMES OF PROXIMAL FEMORAL NAIL ANTIROTATION (PFNA) FOR UNSTABLE INTERTROCHANTERIC FEMORAL FRACTURES - Shah, Syed Waris Ali; Aslam, Muhammad Zeeshan (Pakistan Armed Forces Medical Journal, 2020)
Objective: To analyze the early outcomes of treatment with proximal femoral nail antirotation (PFNA) in patients with unstable intertrochanteric femoral fracture. Study Design: Retrospective cross-section study. Place and Duration of Study: Pakistan Naval Ship (PNS) Shifa Hospital Karachi, from Jan 2015 to Dec 2016. Methodology: Non-probability convenience sampling was used to include unstable intertrochanteric femoral fractures which were treated with proximal femoral nail antirotation. Outcomes were measured in terms of operating time, per-operative blood loss, postoperative weight bearing and complications. Results: A total of 35 patients were analyzed. Mean age was 69.7 years (range 48-91, standard deviation (SD) ± 2.28). There were 18 males (51.4%) and 17 females (48.6%) patients. Majority of fractures were Arbeitsgemeinschaft für Osteosynthesefragen/Association for the Study of Internal Fixation (AO/ASIF) type 3-1-A-2.3 and were seen in 16 patients (45.7%). Average operative time was 39.8 minutes (range 20-85 minutes SD ± 12.38). Mean intra-operative blood loss was 27.7ml (range 15 to 45 ml SD ± 9.18). Two patients (5.7%) had superficial surgical site infection. Post-operatively 16 patients (45.7%) were mobilized full wight bearing with support and 18 patients (51.4%) were mobilized partial weight bearing. Results of current study are quite promising as all fractures subsequently healed without significant complications. Conclusion: Proximal femoral nail antirotation is asuitable implant for unstable intertrochanteric femoral fractures as it is minimally invasive, has no significant blood loss and being intra-medullary early post-opweight bearing can be started.